2022
DOI: 10.1186/s13045-022-01322-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiles of regulatory T cells and their adaptations to the tumor microenvironment: implications for antitumor immunity

Abstract: Characterized by the expression of the critical transcription factor forkhead box protein P3, regulatory T (Treg) cells are an essential part of the immune system, with a dual effect on the pathogenesis of autoimmune diseases and cancer. Targeting Tregs to reestablish the proinflammatory and immunogenic tumor microenvironment (TME) is an increasingly attractive strategy for cancer treatment and has been emphasized in recent years. However, attempts have been significantly hindered by the subsequent autoimmunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 184 publications
0
70
0
Order By: Relevance
“…Immunotherapy of BC has proved to be a challenge in the era of personalized treatment. The interaction between cancer cells and the immune system is a complex, dynamic, and constantly changing process (36). Unlike targeted therapy and endocrine therapy, which effectively guide attacks by identifying targets with biological markers, there are no therapeutic markers for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy of BC has proved to be a challenge in the era of personalized treatment. The interaction between cancer cells and the immune system is a complex, dynamic, and constantly changing process (36). Unlike targeted therapy and endocrine therapy, which effectively guide attacks by identifying targets with biological markers, there are no therapeutic markers for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell infiltration was compared between the low-risk and high-risk groups, and the level of immune cell infiltration, including macrophages and Tregs, was found to be elevated in the high-risk group compared to the low-risk group. An increase in tumor-associated macrophages and Treg cells can create a suppressive immune microenvironment that is associated with poor patient prognosis ( 29 31 ). Treg infiltration was increased in tumor tissues of patients with CCA, suggesting that it may be related to the development of CCA ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a prospective clinical trial, 28 eyes with refractory GVHD–DED exhibited substantial relief after treatment with exosomes from MSCs, showing reduced fluorescein scores, longer tear breakup time, increased tear secretion, and lower OSDI scores ( 130 ). Regulatory T cells (Tregs) have a critical role in the immune system by maintaining immune homeostasis and preventing the occurrence of autoimmune diseases ( 131 , 132 ). It has been demonstrated that early post-transplantation treatment of patients with expanded Tregs + BETi (a bromodomain and extraterminal protein inhibitor) improved the level of Tregs and exhibit a significant diminution of GVHD clinical scores with less ocular involvement ( 133 ).…”
Section: Pathogenic Mechanism and Novel Therapeutic Targetsmentioning
confidence: 99%